Les aménités environnementales : quelle contribution au développement des territoires ruraux? - Amédée Mollard; Christophe Boschet; Jean-Christophe Dissart; Anne Lacroix; Mbolatiana Rambonilaza; Dominique Vollet (VertigO, 2015)
Environmental amenities are sources of enjoyment and attractiveness for tourists and visitors of a territory whose specifity is related to quality natural resources. However, since access to these amenities is free (public goods, neither rival nor excludable), their economic enhancement is not straightforward because specific conditions have to be met. Using analyses carried out in three French regions (Aquitaine, Auvergne and Rhône-Alpes), this article shows that effective enhancement of an amenity potential for rural development purposes requires several conditions related to both site quality and stakeholder strategies. In particular, the identity of the territory must be clear and tied to valued environmental amenities and also that there be a proven link between these amenities packages and the quality of goods and services available on these territories due to the support of and proper coordination between public and private stakeholders.